KAJIAN REVISI UNDANG-UNDANG NO.5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Alynudin, Suhud; Rawinarno, Tjahyo (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2018)
Law Number 5 Year 2014 on State Civil Apparatus (ASN) is in the process of amendment in the House of Representatives. The discussion process has been conducted since the end of 2016 with the focus of discussion related to K-2 honorary staff, KASN existence and ASN management. Amendment of the law as a response of the House of Representatives to the wave of demonstrations conducted by K-2 honorary workers. The amendment law is intended to complement, improve or refine existing. Therefore, the amendment of law No. 5 of 2014 on ASN needs to be done carefully with various considerations in the goal that the law will be more able to provide an integral law for the State Civil Apparatus (ASN).